Al- Najjar, Abdul-Majid. “Belief and ʿUmrān,” Year 2, Issue 8 (Spring 1416 AH/ 1997 CE), Pp. 39-84. - النجار, عبدالمجيد عمر (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 1997)
Abdul-Majid al-Najjar’s study establishes a foundation for the philosophy of anthropology and sociology in Islam. It explains the concept of belief in the existence and attributes of God, the relationship between belief and righteous life, the practical benefits brought about by belief, the effect of belief in God on the purification of the soul, tranquility and security, dignity and power, the purification and liberation of thought, the expansion of perspective, and purification of acts. His study further addresses the effect of belief in God on the purification of the group and the consequent unity of the community, unity of feeling, loyalty, purpose, and liberating the community from internal and external constraints that obstruct the collective will and capacity, and the effect of belief in social solidarity in society.